Technology matters: The efficacy of virtual realistic job preview and its effect on job commitment in hybrid staffing context - Song, Xiaochuan; Vardarlıer, Pelin (Springer Science and Business Media Deutschland GmbH, 2023)
Realistic job preview (RJP) has been considered an effective way for organizations to provide job candidates with snapshots of both positive and negative aspects of the jobs they apply for. However, research on examining the efficacy of virtual reality-assisted RJP (VR-assisted RJP) is still limited, not to mention the examination of VR-assisted RJP’s capacity on predicting person-organization fit (P-O fit) and person-job fit (P-J fit) and turnover. In this chapter, we review the development of RJP in the past few decades and the development of VR-assisted RJP and discuss concerns of VR-assisted RJP. Implications and future research directions are discussed.
Keywords: Person-Job Fit; Person-Organization Fit; Realistic Job Preview; Turnover; Virtual Reality